Encountering the Religious Radicalism Movement Through Reconstructing the Multicultural Theology and Its Implication For Christian Leaders in Indonesia - Gunaryo Sudarmanto; Dina Elisabeth Latumahina (Analisa: Journal of Social Science and Religion, 2020)
This research aims to create a harmonious relationship among different religions in Indonesia. This aim is reached through reconstructing a multicultural theology based on biblical understanding. The multicultural theology is a biblical principle that be constructed in balancing between Old Testament and New Testament, between general revelation and special revelation. By exposing the general revelation based on theocentric dimension, we found general principles about how to make a good relationship among people in their differences, according to God’s perspective. At the same time, multicultural theology also exposes particular revelation principles centered upon the Christocentric dimension. This research is a qualitative study with a library approach. Data is analyzed by interpretation, critical thinking, and truth and healthy consideration based on the primary source.  We found a Christian value to be a foundation to make the relationship in harmony with other people. For this purpose we are proposing a theological framework designed from Biblical principles,   covering the following: (1) Cultural   Mandate, (2)  Human Nature, (3)  Theological principles: God’s  Sovereignty,  God’s  Providence and  God’s Justice, (4) Incarnation, (5) Universal Soteriology (6) Present Theocracy, (7) Church Nature and (8) Eschatological Multiculture. Christian leaders are central people that must create a relationship with other people in harmony. Through this way, the Christian leaders can engage the religious radicalism by doing good things and togetherness in social work.